A review of ophthalmic manifestations of inflammatory bowel disease and associated treatments. Issue 6 (November 2021) - Janardhana, Priya; Al-Kadhi, Saad
Abstract : Purpose of review: To review the ocular manifestations of inflammatory bowel disease (IBD) and the treatments for each of these, including novel therapies and their effects on uveitis. With the advent of newer treatments for ulcerative colitis and Crohn's disease, it is important to investigate whether these therapies have beneficial effects for extraintestinal manifestations (EIM) of IBD, in particular, ocular manifestations. Recent findings: The newer treatments for IBD, including biologics, such as golimumab (Simponi), certolizumab (Cimzia), vedolizumab (Entyvio), and interleukin (IL) receptor inhibitors, such as ustekinimab (Stelara), could potentially have treatment benefits for patients with uveitis and IBD. Summary: Ocular manifestations of IBD are important to detect early and treat appropriately. With novel treatments for IBD, it is important to further study whether these therapies have benefits for ocular manifestations of IBD, such as uveitis. Future clinical trials need to be conducted to investigate this.